2022
DOI: 10.1016/j.jctube.2021.100292
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tuberculosis drug resistance in Slovakia, 2018–2019: The first whole-genome epidemiological study

Abstract: Highlights The Euro-American lineage 4.7 was the most represented among the XDR-TB/MDR-TB resistant strains. Seven of 12 isolates (58%) belonged to the same recent transmission chain. Strains originally from Eastern European countries were diagnosed in patients without any epidemiological links with these countries. Incidence of resistant XDR-TB/MDR-TB in Slovakia, while low, still should be taken to monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previous studies conducted in Ukraine, the Russian Federation and other Central Asian countries showed similar results [ 25 27 ]. The results also showed changes in the distribution of lineages in Slovakia, with a predominance of the Beijing lineage, which occurred in only 2 patients over the last 6 years [ 16 ]. As this lineage is characterized by increased virulence and transmissibility, we strongly recommend public health authorities to take the necessary measures, such as a thorough investigation of close contacts, as early detection facilitates rapid initiation of an appropriate treatment regimen [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted in Ukraine, the Russian Federation and other Central Asian countries showed similar results [ 25 27 ]. The results also showed changes in the distribution of lineages in Slovakia, with a predominance of the Beijing lineage, which occurred in only 2 patients over the last 6 years [ 16 ]. As this lineage is characterized by increased virulence and transmissibility, we strongly recommend public health authorities to take the necessary measures, such as a thorough investigation of close contacts, as early detection facilitates rapid initiation of an appropriate treatment regimen [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and WGS were performed as mentioned above (see section Ukrainian refugees and migrants). Twelve MDR and pre-XDR isolates have been described previously (accession number PRJEB43174) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…TB control efforts of low-incidence regions can be compromised due to transmission events between native patients and immigrants with drug-resistant Mycobacterium tuberculosis (MTB) isolates, especially MDR-TB isolates. Some studies have reported transmission events between native patients and foreign patients with MDR-TB isolates in Germany, Switzerland, Slovakia, and Belgium using whole-genome sequencing (WGS) [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The illness affects the respiratory tract in so‐called pulmonary TB and the extrapulmonary form of the disease is recognized in M. tuberculosis infection sites other than the lungs. In the Slovak Republic, a low TB burden country, the incidence of both drug‐susceptible and drug‐resistant forms of TB remains relatively stable 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…In the Slovak Republic, a low TB burden country, the incidence of both drug‐susceptible and drug‐resistant forms of TB remains relatively stable. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%